2020
DOI: 10.1002/tsm2.222
|View full text |Cite
|
Sign up to set email alerts
|

Head injury and concussion in cricket: Incidence, current guidance, and implications of sports concussion literature

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…Descriptions of how various neurological symptomology may present following head impact have been attempted but agreed definitions have not been made thus far [12]. Furthermore, previous work within cricketing populations has suggested atypical presentation following impact [13]. To further complicate, symptoms and signs from brain injury can evolve and present sub-acute, which require evaluation at, as yet unspecified time periods.…”
Section: Elite Level Cricketmentioning
confidence: 99%
“…Descriptions of how various neurological symptomology may present following head impact have been attempted but agreed definitions have not been made thus far [12]. Furthermore, previous work within cricketing populations has suggested atypical presentation following impact [13]. To further complicate, symptoms and signs from brain injury can evolve and present sub-acute, which require evaluation at, as yet unspecified time periods.…”
Section: Elite Level Cricketmentioning
confidence: 99%
“…CogSport performance and symptoms relative to intraindividual baselines are reported in table 1. The median total number of symptoms reported on CogSport on the day of head injury was 7 out of 24 (IQR 5-11) and symptom severity was 10 out of a possible 120 (IQR [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Cogsport Performance and Symptoms On The Day Of Injury For Concussed Playersmentioning
confidence: 99%
“…[6][7][8] Reproducible tests such as these are also useful in monitoring an athlete's neurocognitive recovery, which can occur on a very individualised timeline. 9 There are a number of different computerised neurocognitive tests used to assess sport-related concussion. A study in 2012 found the Computerised Cognitive What are the new findings ► Neurocognitive testing, such as CogSport, is a useful clinical adjunct tool to assist the diagnosis of concussion following head impact in elite cricket players.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, cricketers have been recently reported to have increased head-related injury rates and delayed recovery. 7 However, concussion risk has been found to be lower in baseball/softball, lacrosse, and field-hockey compared to other contact sports. 3 An exception to this was ice-hockey where 8 concussion was one of the most reported injuries in male players.…”
Section: Introductionmentioning
confidence: 99%